IMPLEMENTASI MONITORING JARINGAN INTERNET PADA MIKROTIK MENGGUNAKAN NOTIFIKASI BOT TELEGRAM DI SMK - Amin, Munawar; Hasbi, Muhammad; Widada, Bebas; Yudanto, Bramasto Wiryawan (STMIK Sinar Nusantara, 2025)
Delays in detecting network issues due to reliance on manual monitoring user and user reports have created significant challenges in network management, particularly in environments requiring consistent internet connectivity, Such as educational institutions. This study aims to implement an internet network monitoring system based on Mikrotik, integrated with Telegram Bot notifications and supported by the Winbox application for manual configurations. The study adopts the Network Development Life Cycle (NDLC) method, ensuring a structured and systematic approach from analysis to management. The results show that the system successfully detects devices statuses in real-time, delivery accurate and timely notifications, and significantly reduces response time in addressing network issues. By enabling administrators to take immediate action, the system ensures stable connectivity, supporting educational and administrative effectively.